Landscape and settlement in Late Bronze Age Cyprus: investigations at Pyla-Kokkinokremos, 2007-2009 - Brown, Michael (Palestine exploration quarterly, 2017)
Pyla-Kokkinokremos is a fortified hilltop settlement in Cyprus founded towards the end of the Late Bronze Age. It has played a prominent role in discussions concerning the c. 1200 BC ‘collapse’ in the wider eastern Mediterranean. Results from survey and soundings (2007-09) provide significant new information about the site and its relationship to the surrounding landscape. This includes the discovery of a large intramural feature in the form of a shallow bedrock terrace with associated architecture running through the centre of the settlement. Consideration is also given to broader regional patterns of settlement in the surrounding Pyla littoral and south-east Cyprus.